1992
DOI: 10.1002/bit.260400121
|View full text |Cite
|
Sign up to set email alerts
|

Batch cultivation of Methylosinus trichosporium OB3b: II. Production of particulate methane monooxygenase

Abstract: The obligatory methanotroph, Methylosinus trichosporium OB3b, was studied to optimize the batch culture conditions for the formation of particulate methane monooxygenase (pMMO) in a nitrate minimal salts medium. The important medium components investigated were copper, carbon dioxide, and nitrate. The whole-cell specific pMMO activity decreased sharply with increasing copper concentrations in the range of 10-40 microM and remained constant upon further increases of the copper concentration to 120 microM. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 15 publications
(6 reference statements)
4
35
0
Order By: Relevance
“…These results confirm that the biofilter should be operated around neutral pH for optimal methanotrophic growth (Humer and Lechner, 1999a;Park et al, 1992).…”
Section: Inoculumsupporting
confidence: 73%
See 1 more Smart Citation
“…These results confirm that the biofilter should be operated around neutral pH for optimal methanotrophic growth (Humer and Lechner, 1999a;Park et al, 1992).…”
Section: Inoculumsupporting
confidence: 73%
“…In a biofilter, NH 3 is converted to nitrous and nitric acid by nitrification and H 2 S is converted to sulfuric acid. At high NH 3 and H 2 S loading rates, methanotrophs may be inhibited by high ammonium and nitrite concentrations (Bedard and Knowles, 1989;Bronson and Mosier, 1993;King and Schnell, 1994;Boeckx et al, 1996;Humer and Lechner, 1999a) or by sulfuric acid accumulation (Furusawa et al, 1984;Yang and Allen, 1994) as the pH optimum of methanotrophs lies between 6 and 8 (Park et al, 1992;Humer and Lechner, 1999a). However, at EBRT's that are common for biofiltration of methane containing air, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The medium used for the two-step experiments was adapted to obtain high cell densities and consisted of a three times higher concentration of all ingredients; only the concentrations of MgSO 4 и 7H 2 O, KH 2 PO 4 , CaNO 3 , and H 2 SO 4 remained unaltered. In the two-step system the cells were grown at 30% of MAX ( MAX ‫ס‬ 0.11 h −1 ; Park et al, 1992) ( L ‫ס‬ 1 mL min −1 ; D ‫ס‬ 0.028 h −1 ) and the following gas flows were used: methane, 19 mL min −1 ; air, 5 mL min −1 , oxygen, 32 mL min −1 . Air was always included to have nitrogen present as an internal standard for GC measurements.…”
Section: Organism and Growth Conditionsmentioning
confidence: 99%
“…Since the V max values of sMMO and pMMO are similar (Table 1), it was concluded that very little methane was dissolved, implying a small K s,S value resulting in a very short methane consumption period (seconds). A simulation using a literature value for the V max,S of pMMO (290 nmol min − 1 mg − 1 , Park et al, 1992) and a K s,S value of 3 vM appeared to give a good representation of the data (Fig. 4B).…”
Section: Pmmo Has a Higher Affinity For Methane Than Smmomentioning
confidence: 81%
“…trichosporium OB3b expresses different methane monooxygenases (MMOs), depending on the amount of copper available (Park et al, 1992). In the absence of copper, a soluble form (sMMO) is expressed.…”
Section: Pmmo Has a Higher Affinity For Methane Than Smmomentioning
confidence: 99%